凸轮激波摆动活齿传动的结构及齿形分析 - 董新蕊; 李剑锋; 隋琰; 王青云; 杨帆; 王新华; 刘志峰 (Jixie chuandong)
A two-teeth difference cam disk profile swing movable driver is introduced, whose transmission principle, structure and characteristics are investigated. The theory and task tooth profile equations of central internal gear are deduced by a new way. After taking off the process to solve the profile curvature, the curvature distribution along the gear profile curve is analyzed. Based on these, the tooth profile is imitated by the MATLAB program, and the effects on the profile’s geometry with the involved parameters are analyzed. All the results can basically assist to the stepped designs and analysis on the internal gear.